2015
DOI: 10.1111/jorc.12142
|View full text |Cite
|
Sign up to set email alerts
|

Patient activation with knowledge, self‐management and confidence in chronic kidney disease

Abstract: Background: Chronic kidney disease is a growing health problem on a global scale. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 23 publications
(44 reference statements)
4
58
2
4
Order By: Relevance
“…Lack of understanding about kidney disease identified in this phase seems to be consistent with that of other research conducted in the U.S. (Johnson et al, 2016;Welch et al, 2016;, Australia (Enworom & Tabi, 2015;Gray, Kapojos, Burke, Sammartino, & Clark, 2016;Wembenyui, 2017), Peru (Anaya et al, 2016), and Iran (Qobadi, Besharat, Rostami, & Rahiminezhad, 2015). This phase found that Vietnamese people had limited knowledge about CKD.…”
Section: Phase One: Translation and Validation Of Instruments 63supporting
confidence: 76%
See 1 more Smart Citation
“…Lack of understanding about kidney disease identified in this phase seems to be consistent with that of other research conducted in the U.S. (Johnson et al, 2016;Welch et al, 2016;, Australia (Enworom & Tabi, 2015;Gray, Kapojos, Burke, Sammartino, & Clark, 2016;Wembenyui, 2017), Peru (Anaya et al, 2016), and Iran (Qobadi, Besharat, Rostami, & Rahiminezhad, 2015). This phase found that Vietnamese people had limited knowledge about CKD.…”
Section: Phase One: Translation and Validation Of Instruments 63supporting
confidence: 76%
“…It is possible that knowledge is a prerequisite for changing behaviour to improve health outcomes of people with CKD (Welch et al, 2016;Wu, Hsieh, Lin, & Tsai, 2016).…”
Section: Self-efficacymentioning
confidence: 99%
“…CKD has a major effect on the individual level by increasing the morbidity and mortality of patients and also increasing healthcare costs and the demand for healthcare services on a national level [1]. With this increasing rate of CKD, increased awareness and understanding of the overall CKD burden is needed, which may lead to improvement in the knowledge, trust, and involvement in selfmanaging the disease [9]. Haemodialysis (HD) is the most common method of treatment, with approximately 90.6% of patients undergoing it.…”
Section: Introductionmentioning
confidence: 99%
“…Covariates for adjustment were chosen according to clinical significance and possible effect on portal adoption (1,(3)(4)(5)(6)(7)(8)10,11,(13)(14)(15)29,31,33,34,36,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). Sociodemographic variables were age, sex, race, marital status, insurance status, neighborhood median household income, tobacco use, and follow-up duration.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Patient activation (the "knowledge, skills and confidence" needed to actively engage in care) (12) is a critical feature of CKD management, wherein BP self-monitoring, dietary modification, medication adherence, nephrotoxin avoidance, and patient-provider collaboration are essential (13)(14)(15)(16). Enabling patients with CKD to easily access their medical information is a novel approach to facilitate patient engagement and activation (17).…”
Section: Introductionmentioning
confidence: 99%